2019
DOI: 10.1002/mrd.23179
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA Gm2044 promotes 17β‐estradiol synthesis in mpGCs by acting as miR‐138‐5p sponge

Abstract: Long noncoding RNAs (lncRNAs) have been demonstrated to play vital roles in mammalian reproduction. Our previous research revealed that lncRNA Gm2044 is highly expressed in mouse spermatocytes and regulates male germ cell function. The gene annotation database BioGPS shows that Gm2044 is not only highly expressed in testicular tissue but also in ovarian tissue, which suggests that Gm2044 may be involved in female reproductive development. In this study, we confirmed that lncRNA Gm2044 promotes 17β‐estradiol sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…In recent years, E2 synthesis in female ovarian GCs has been proved to be regulated by a bunch of epigenetic regulation factors including miRNAs, circRNAs, and lncRNAs (Li et al, 2018a;Huang et al, 2020). For lncRNAs, only lncRNA-Gm2044 (Hu et al, 2019) and lncRNA-SRA (Li et al, 2018b) have been proved to influence E2 synthesis and secretion in mammalian ovarian GCs through regulating the expression of Cyp19a1, but which are all studied in mice. However, it is still unclear whether lncRNAs can regulate E2 synthesis in porcine ovarian GCs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, E2 synthesis in female ovarian GCs has been proved to be regulated by a bunch of epigenetic regulation factors including miRNAs, circRNAs, and lncRNAs (Li et al, 2018a;Huang et al, 2020). For lncRNAs, only lncRNA-Gm2044 (Hu et al, 2019) and lncRNA-SRA (Li et al, 2018b) have been proved to influence E2 synthesis and secretion in mammalian ovarian GCs through regulating the expression of Cyp19a1, but which are all studied in mice. However, it is still unclear whether lncRNAs can regulate E2 synthesis in porcine ovarian GCs.…”
Section: Introductionmentioning
confidence: 99%
“…The RNA of male germ cells was reverse transcribed to cDNA by the Evo M-MLV RT Kit (Accurate Biotechnology, Changsha, P. R. China) with RTase Reaction Buffer Mix, Evo M-MLV RTase Enzyme Mix, Oligo dT (18T) Primer and Random 6 mers Primer at 37°C 15 min, 85°C 5 s and 4°C hold. Afterwards, the cDNA was analyzed by RT-qPCR to study lncRNA-Gm2044 and mRNA expression using the SYBR Green Premix Pro Taq HS qPCR Kit (Accurate Biotechnology) at 95°C 30 s, 40 cycles of 95°C 5 s and 60°C 30 s. The primers for lncRNA-Gm2044 and β-actin (internal reference) are listed in our previous research ( Hu et al, 2018 , 2019 ), and other primers are shown in Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, RT-qPCR kits (Accurate, Changsha, China) were performed to identify the targeted gene expression (Suppl. Table S1); the β-actin primers were designed with reference to the previous report (Hu et al, 2019;Yao et al, 2014). The expression was normalized to ACTB (β-actin) using the comparative 2-ΔΔ Ct method for the expression level of the target gene (Yao et al, 2014).…”
Section: Real-time Quantitative Polymerase Chain Reaction (Rt-qpcr)mentioning
confidence: 99%